Are battlefield and prehospital trauma scenarios an effective educational tool to teach leadership and crisis resource management skills to undergraduate medical students?. Issue Volume 166:Issue E(2020) (17th June 2019) - Ellington, Matt; Farrukh, S
Abstract : Introduction: Leadership and crisis resource management (CRM) skills are important skills for doctors, however there is a recognised lack of undergraduate leadership education. There remains debate over how best to teach leadership and CRM skills, and poor leadership skills among clinicians are associated with adverse patient outcomes. We examined whether high-fidelity battlefield and prehospital scenarios can improve leadership and CRM skills. Method: This was a prospective observational study with students self-reporting their leadership and CRM skills using the Ottawa Crisis Resource Management Global Ranking Scale (OCRMGRS) before and after completing the Cambridge University Emergency Medicine Society Battlefield and Pre-Hospital Trauma course. The course involves a mixture of small group tutorials and practical high-fidelity battlefield and prehospital trauma scenarios. Faculty also completed the OCRMGRS for the first and last candidates at the scenarios. The mean precourse versus mean postcourse score of the OCRMGRS was analysed using a two-tailed t-test. Results: 46 students completed paired OCRMGRS before and after the course. The mean precourse scores for each of the domains (leadership, communication skills, resource utilisation, problem solving skills and situational awareness) were calculated. There was a statistically significant (p<0.05) increase in both self-reported and faculty-reported scores across all domains, and the increase remained at 1-year follow-up. Conclusions: Leadership and CRM skills are important non-clinical skills for doctors, however there is debate over how best to teach them. High-fidelity battlefield and prehospital trauma scenarios are an effective means of teaching leadership and CRM skills to civilian medical students.